Aplicación del proceso de atención de enfermería con afrontamiento al estrés percibido de la comunidad de Pamplona, Colombia - Mogollón-Gauta, Karol Yerleyza; Barajas-Lizarazo, Mayra Alejandra; Escobar-Velásquez, Katty Dayana (Duazary, 2025)
Effective coping with community stress is solving collective problems by optimizing existing internal and external resources. A case study of a community in Pamplona, Norte de Santander, is presented, which presented dissatisfaction and distress at the time of the nursing assessment due to the lack of correct practices for garbage disposal. The application of the nursing care process contributed to the active participation of the community in complying with environmental health standards through awareness processes, ecological education, control strategies, and minimization of health risks.